Occupational risk management in construction supply chain - Barreto, Matheus de Faria e Oliveira (2024)
The building is historically a driver of the economy, creating thousands of direct and indirect jobs, moving a huge chain of suppliers of raw materials, supplies and services, besides building a country’s infrastructure and the homes of millions of people. But working conditions in this sector that is so important to the country are not the best, exposing workers to risks of work accidents and occupational diseases. Therefore, this study sought to present the main occupational hazards in the construction industry, discussing alternatives for effective risk management by reducing the rates of accidents and illness among workers. In this research, case studies were done in small and medium-sized construction sector facing the residential construction market. It was also proposed solutions for the implementation of risk management and occupational health and safety for businesses to succeed and lower the rates of accidents at work, health and safety, and quality of work life in these companies.